Women's Volunteering and Voluntary Leadership Positions in Sport—Secondary Analyses of the German Survey on Volunteering - Burrmann, Ulrike; Sielschott, Stephan (Frontiers in Sports and Active Living, 2022)
For decades, the German sports policy mission statement “Sport for All” has been aimed at attracting women to voluntary work in the sports sector. Nevertheless, women are consistently underrepresented in volunteering within sports organizations and especially on boards. One-dimensional gender analyses that exclude other factors like class and ethnicity cannot, however, adequately describe different modes of disadvantage. In order to analyze the unequal access to volunteering and leadership positions in sport, we refer to inequality theory and intersectional approaches, which include different factors of disadvantage. Our study is based on a quantitative population survey on volunteering in Germany with more than 25,000 respondents conducted in 2014 and 2019. We examine factors and interactions that can predict women's volunteering and leadership in sport. The results show that the proportion of women who volunteer is lower than the proportion of men and that fewer women than men take on leadership positions. The gender differences were not as pronounced in 2019 as they were in 2014. Independent of gender, the likelihood of volunteering increases with higher income, A-levels, no immigration status, marriage and the presence of children in the household. Part-time and marginal employment is more often associated with volunteering among women than among men; however, the likelihood of volunteering decreases more for women than for men when they are not employed at all. Moreover, higher income for women is less likely to be associated with voluntary work than for men while volunteering in other areas has a more positive effect on volunteering in sports for women than for men. Independent of gender, the likelihood of holding a leadership position increases with higher income, with marriage, and decreases with immigration background and with the presence of children in the household. Part-time and marginal employment increase the likelihood of having a leadership position to a greater extent for men than for women. In terms of leadership positions men benefit more than women if there are no children in the household. The results suggest that practical and policy efforts should focus more on improving the conditions for women to gain voluntary leadership positions.